Comparative Analysis of Corporate Governance and Financial Performance of Indian Banking Sector: An Empirical Case Study of ICICI and SBI Bank (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
As organisations expand and grow, corporate governance has gained widespread attention as a means of revealing greater responsibility and transparency. The system of structural, administrative, and cultural safeguards known as corporate governance (CG) is intended to make sure that an organisation is managed in the long-term best interests of its stakeholders. The goal of this research project is to examine the origins and principles of corporate governance, with a particular focus on banks, in order to compare the corporate governance strategies used by ICICI and SBI. Comparatively speaking, this study also examined the financial performance of SBI Bank and ICICI Bank, paying particular attention to their positions in terms of profitability, solvency, and liquidity. The current study is primarily empirical and is supported by secondary data. The objective of this research is to examine the corporate governance framework and compare the financial performance of SBI Bank with ICICI Bank. The researchers used financial data spanning five years, from March 31, 2018, to March 31, 2022, to analyse the financial performance of India's banking industry. The independent sample t-test was employed in this investigation to assess the hypotheses. The following ratios are calculated for this purpose: net profit, quick ratio, debt-to-equity, interest coverage ratio, gross profit, and current ratio. The findings show that the SBI and ICICI current ratio was not recorded in accordance with the 2:1 normal rules of the CR. However, the liquid ratio for SBI and ICICI was found to be extremely high. SBI and ICICI's liquidity positions are not accurately documented. It was discovered that SBI's NPR showed a varying tendency with regard to profitability. However, ICICI Bank continues to be stable. Both SBI and ICICI's solvency positions are reported as being in good standing. Moreover, ICR and DER continue to be uniform.